Manajemen Perkawinan Adat Kei di Ohoi Waur Kecamatan Kei Besar Kabupaten Maluku Tenggara - Johanis Baptis Janjaan; Rudolf Kempa; Arnold Sahalessy (Jurnal Pendidikan Geografi Unpatti, 2025)
The implementation of traditional marriage in the Kei region is a complex cultural legacy rooted in strong social values. The community of Ohoi Waur in Kei Besar District continues to uphold customary marriage practices based on the hierarchical and collective Larvul Ngabal customary law. This study aims to analyze how social management practices operate within traditional structures through processes of planning, organizing, implementation, and evaluation. This research employed a descriptive qualitative approach using participatory observation, in-depth interviews, and documentation techniques. Findings reveal that managerial practices in customary marriages are not spontaneous but are embedded within role distribution patterns, social control, and coordination mechanisms among families and customary leaders. These patterns demonstrate the internal capacity of the community to manage inherited values through adaptive traditional structures. The study offers a new perspective that local management systems can serve as an organized and directed basis for social governance. The implication encourages community-based cultural preservation policies, with a recommendation to replicate this research in other customary communities to enrich local social practice mapping.